Alternate Pathway for Isoleucine Biosynthesis in Escherichia coli - Phillips, A. T. (1972)
A threonine dehydrataseless mutant of Escherichia coli, Crookes strain, was observed to grow on an acetate minimal medium without the usual requirement for isoleucine supplementation. Both the wild-type Crookes strain and a threonine auxotroph metabolized l-glutamate-1-(14)C to l-isoleucine-1-(14)C with no appreciable randomization, suggesting that a pathway for isoleucine formation from glutamate via β-methylaspartate, β-methyloxaloacetate, and α-ketobutyrate was possible in addition to the pathway from threonine and α-ketobutyrate. Crude cell-free extracts formed (14)C-β-methylaspartate from (14)C-glutamate, and the conversion of β-methylaspartate to α-ketobutyrate was also demonstrated, thus supporting the conclusion that glutamate can serve as a precursor of α-ketobutyrate (and isoleucine) without the necessary involvement of threonine as an intermediate.